2011
DOI: 10.1590/s1984-82502011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of moisture content in lyophilized mannitol through intact glass vials using NIR micro-spectrometers

Abstract: Determination of moisture content in lyophilized solids is fundamental to predict quality and stability of freeze-dried products, but conventional methods are time-consuming, invasive and destructive. The aim of this study was to develop and optimize a fast, inexpensive, noninvasive and nondestructive method for determination of moisture content in lyophilized mannitol, based on an NIR micro-spectrometer instead of a conventional NIR spectrometer. Measurements of lyophilized mannitol were performed through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This aspect is similar to that of NIR methods. The major advantage of TD NMR over KF, which is the gold standard for measuring total water content in pharmaceutical formulations, is that, like NIR methods, it is nondestructive and noninvasive. Besides that, the total experimental time per sample was reduced to less than 5 min, bringing an additional advantage over KF, which has longer sample preparation and measurement times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This aspect is similar to that of NIR methods. The major advantage of TD NMR over KF, which is the gold standard for measuring total water content in pharmaceutical formulations, is that, like NIR methods, it is nondestructive and noninvasive. Besides that, the total experimental time per sample was reduced to less than 5 min, bringing an additional advantage over KF, which has longer sample preparation and measurement times.…”
Section: Resultsmentioning
confidence: 99%
“…An ideal method should perform fast, noninvasive, and nondestructive measurements with minimal or no sample preparation. Near infrared (NIR) is such a method that has been established by Muzzio et al, who showed that lyophilized mannitol can be thoroughly examined for moisture content without modifying the content of the lyophilized vials . Moreover, several reports have also been published for the determination of moisture content in lyophilized products by scanning through the bottom of vials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Grohganz et al (2009) also demonstrated a NIR technique for quantification of water in freeze-dried lyophilized mixtures and showed good model accuracy with a low error. Muzzio et al (2011) used NIR combined with PCR and PLS analysis for the prediction of water contents in lyophilized mannitol (mannitol was used as an excipient in lyophilized pharmaceutical products). The obtained results suggested that both PCR and PLS models are able to predict moisture content, with   of 0.99 (calibration) and 0.96 with RMSEP of 0.233% respectively.…”
Section: Moisture Contentmentioning
confidence: 99%
“…An example of the use of PLS to determine moisture from NIR can be found in a study to develop and optimize a fast, inexpensive, noninvasive, and nondestructive method for determination of moisture content in lyophilized mannitol, based on an NIR microspectrometer instead of a conventional NIR spectrometer. (Muzzio et al 2011). b.…”
Section: Lyophilization Application Examplesmentioning
confidence: 99%